Yield and protein content of three kiwicha varieties under three fertilization levels in Marcará, Ancash 2022 (Aporte Santiaguino, 2025)
Three levels of inorganic fertilization with nitrogen, phosphorus, and potassium were applied to Amaranthus caudatus L. (kiwicha) crops in order to evaluate their effects on protein content and grain yield. The experiment included the varieties “Óscar Blanco,” “Centenario,” and “Caracino,” and three NPK treatments (40-40-40; 100-90-60; 120-150-80). A randomized complete block design with a 3×3 factorial arrangement and four replications was used. Fertilization was applied in two stages: the first at 30 days after sowing, and the second at 60 days. The variables analyzed were grain yield, plant height, and protein content. Results showed that the fertilization levels 120-150-80 and 100-90-60 produced the highest yields (2,415.4 and 2,382.3 kg/ha, respectively), while the 40-40-40 dose reached only 1,909.9 kg/ha. Regarding cultivars, “Óscar Blanco” and “Centenario” showed no significant difference in yield (2,408.1 and 2,350.3 kg/ha), and both outperformed “Caracino,” which had a lower yield of 1,949.7 kg/ha. In terms of protein content, “Óscar Blanco” and “Centenario” also had higher values (14.88% and 14.64%) compared to “Caracino” (13.59%). As for plant height, “Centenario” and “Óscar Blanco” reached 1.18 m and 1.15 m, respectively, while “Caracino” was shorter at 1.04 m.
Keywords: Kiwicha; Cultivar; Fertilization; Yield; Amaranthus caudatus L